Synovial chondromatosis of knee joint: a case report - Bezawada, Paparao; Yadlapalli, Saipramod; Katta, Hari Chandana (International Journal of Research in Orthopaedics, 2022)
Synovial chondromatosis is a benign condition encountered infrequently within joints which is also known as synovial osteochondromatosis. They present as multiple nodules in the synovium which are either fibrin type or cartilaginous type. The fibrin type usually results from bleeding within the joint, rheumatoid arthritis and tuberculosis. The cartilaginous type is usually due to trauma or osteoarthritis. This typically involves large joints, knee being the most common, rarely small joints also may be involved. Here we report a case of 30-year-old female who presented to us with symptoms of swelling, restriction of movement and pain in the right knee. After clinical and radiological assessment, arthroscopic exploration with loose body removal and synovectomy done, following which patient achieved painless complete range of movements. Histopathological examination confirmed the diagnosis as synovial chondromatosis.